Exercise workload: a key determinant of immune health – a narrative review - Shi, Xinxin; Hu, Lunuo; Nieman, David C.; Li, Fei; Chen, Peijie; Shi, Hui; Shi, Yue (Frontiers in Immunology, 2025)
The total exercise workload is an important factor influencing immune health. Appropriately prescribed physical activity can mitigate the detrimental effects of chronic inflammation, bolster the body’s defenses against both infectious and non-infectious diseases, and decelerate the immunosenescence process. Physiological and immune system responses to moderate and strenuous exercise workloads vary markedly. This narrative review summarizes current findings on the impacts of moderate-intensity exercise, high-intensity interval training, and strenuous and prolonged exercise on immune health, elucidating their specific effects and underlying mechanisms. Additionally, the role of challenging environmental conditions in shaping immune responses to exercise is also briefly considered. The insights presented here are intended to guide healthy individuals in selecting evidence-based exercise training protocols that are compatible with both health promotion and immune health. Moreover, this review offers prospective research directions, particularly regarding personalized exercise regimens and the interaction between exercise and environmental factors, providing valuable perspectives for scholars within the field of exercise immunology.